Biblical Geography in Southwestern Judah - Hardin, James W. (Near Eastern archaeology, 2012)
Scholars have studied the region around Wadi el-Hesi for 175 years. In the past they identified the region around Tell el-Hesi as Judahite, but most recently the scholarly consensus has shifted to Philistine. Both archaeological survey and excavation of the Hesi region support a Judahite identification. In this article the authors examine the case of Tell el-Hesi and its environs being Judahite from the eleventh through the eighth centuries B.C.E., then suggest implications for this interpretation. If the Hesi region was Judahite, then the Lachish district as defined in Josh 15:37–41 extended much further west than is usually assumed. Once this is recognized, it is possible to suggest identifications for three currently unidentified sites: Zenan (Khirbet Summeily), Hadashah (Tel Sheqef), and Migdal Gad (Tell el-Hesi).